Esophageal cancer burden attributable to alcohol use and low consumption of vegetables from 1990 to 2021 across countries with different sociodemographic characteristics - Yi-Kai Ma; Yue-Ting Zhou; Cai-Xia Liu (Journal of Nutritional Oncology)
Abstract. Background:. Esophageal cancer (EC) is a lethal malignancy. The sociodemographic index (SDI) is a critical factor influencing the disease burden of EC. Risk factors, including alcohol use and diet, vary significantly by SDI level, affecting the disease outcomes. This study utilized the Global Burden of Disease Study 2021 database to determine the age-standardized mortality rates (ASMR) and age-standardized disability-adjusted life-year rates (ASDRs) for EC attributable to alcohol use and a diet low in vegetables across countries with different SDI. Methods:. Data from the Global Burden of Disease Study 2021, covering from 1990 to 2021, were analyzed for 204 areas categorized into quintiles based on the SDI. Exposure levels for alcohol and vegetable intake were defined, and data were standardized using the global population structure to ensure comparability. Trend lines for the disease burden were plotted using R version 4.3.0 (R Foundation for Statistical Computing, Vienna, Austria). Statistical analyses were conducted using Joinpoint 4.9.1.0 (The Division of Cancer Control and Population Sciences, USA) regression to assess temporal trends in mortality and ASDRs, focusing on the annual percent change and average annual percent change across various SDI categories. Results:. From 1990 to 2021, the ASMR and ASDR for EC decreased globally across all SDI levels and in both sexes. The areas with a middle SDI initially had the highest rates but experienced the fastest declines, falling below high-middle–SDI countries by 2021. The ASMRs attributable to alcohol use generally declined, except in low-middle– and low-SDI nations. The greatest rates among males and the total population were found in high-middle–SDI nations, whereas high-SDI nations had the highest rates among females. The ASMRs associated with a diet low in vegetables decreased in all areas. Conclusions:. Despite the overall declining trend in the EC burden associated with alcohol use and diets low in vegetables, EC remains a significant global health concern. Strengthening the focus on key populations, implementing public health policies to reduce alcohol consumption, and promoting increased vegetable intake may collectively reduce the global burden of EC.